An Authenticated Key Agreement Protocol Using Artin’s Braid Group - Chaturvedi, Atul; Misra, Manoj Kumar; Tripathi, S P; Shukla, Varun (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a new and efficient key agreement protocol where trusted third party (TTP) is involved. There are various available schemes which are based on number theoretic, elliptic curves etc. Due to the availability of modern computers, these schemes are vulnerable to man in the middle attack (MITM). So there is a requirement of new technique for key agreement which surprises the intruders and enhances the security of communication system. Our proposed protocol utilizes the property of a non commutative group. We have given the security proof of our protocol keeping the fact in mind that decomposition and conjugacy search problem are hard in a group which is non commutative.